Activation of Factor IX by Factor XIa - A Spectrophotometric Assay for Factor IX in Human Plasma - Tans, G; Janssen-Claessen, T; van Dieijen, G; Hemker, H C; Rosing, J (Thrombosis and Haemostasis, 1982)
The activation of Factor IX by partially purified Factor XIa was followed by active site titration, gelelectrophoresis and by a spectrophotometric assay. The assay is based on the finding that the rate of Factor X activation in the presence of phospholipid and Ca2+ is linear in time and proportional to the amount of Factor IXa present and can be determined with the chromogenic substrate S2222. Conditions were found that allowed complete activation of Factor IX in human plasma by Factor XIa. The amount of Factor IXa present in the plasma sample can be determined with the spectrophotometric assay and is proportional with the amount of plasma present. In plasma from patients receiving vitamin-K antagonists reduced Factor IX activity is found with the spectrophotometric assay, and the new assay method may be useful in monitoring oral anticoagulant therapy.
Keywords: Active site titration of F IXa; Activation of F IX by F XIa; Spectrophotometric assay for F IXa; Chromogenic substrate; Factor XIa; Factor IX; Hemophilia B